Pemanfaatan Minyak Jelantah menjadi Pembersih Lantai bagi Masyarakat Desa Siku Kabupaten Muara Enim - Indri, Wanda Indriani; Mutmainah Juniawati (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2023)
This community service activity is a form of collaboration between students of the Raden Fatah State Islamic University Palembang Real Work Study Program with Siku Village, Empat Petulai Dangku District, Muara Enim Regency, South Sumatra Province by providing education about the negative impacts of used cooking oil waste on health and the surrounding environment, as well as training the utilization of used cooking oil into a product that can be utilized by the people in the village. Where used cooking oil itself is used frying oil that is used continuously and is black and smells rancid. The purpose of this activity is to prevent environmental pollution caused by used cooking oil which is processed into floor cleaning products for the people of Siku village. The method used in this study was education about the dangers of used cooking oil, as well as training in using used cooking oil as a floor cleaner. The result of this activity is that the community knows about the dangers of used cooking oil waste and training on using used cooking oil provides new knowledge to the people of Siku village. The hope is that after this community service there will be no more used cooking oil waste that is thrown away carelessly and can be managed by the community so that environmental pollution does not occur.